2005
DOI: 10.1208/pt060242
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dialysis in vitro release method for biodegradable microspheres

Abstract: The purpose of this research was to develop a simple and convenient in vitro release method for biodegradable microspheres using a commercially available dialyzer. A 25 KD MWCO Float-a-Lyzer was used to evaluate peptide diffusion at 37°C and 55°C in different buffers and assess the effect of peptide concentration. In vitro release of Leuprolide from PLGA microspheres, having a 1-month duration of action, was assessed using the dialyzer and compared with the commonly used ''sample and separate'' method with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 34 publications
(30 reference statements)
0
71
0
Order By: Relevance
“…15 Briefly, a predetermined amount of microspheres were transferred to the Float-a-Lyzer and suspended in 5 mL of 0.1 M phosphate buffered saline (PBS) pH 7.4. The dialyzer was then introduced into a graduated glass cylinder containing 55 mL buffer at 37-C.…”
Section: Long-term Peptide Releasementioning
confidence: 99%
See 1 more Smart Citation
“…15 Briefly, a predetermined amount of microspheres were transferred to the Float-a-Lyzer and suspended in 5 mL of 0.1 M phosphate buffered saline (PBS) pH 7.4. The dialyzer was then introduced into a graduated glass cylinder containing 55 mL buffer at 37-C.…”
Section: Long-term Peptide Releasementioning
confidence: 99%
“…In a previous study, 15 a novel dialysis technique using a commercially available dialyzer composed of a regenerated cellulose membrane was used to assess peptide diffusion at varying temperatures and release from PLGA microspheres at 37-C. Results from the diffusion and in vitro release studies on peptide-loaded microspheres revealed the advantages of this technique over the commonly used "sample and separate" method including ease of sampling, total buffer replacement, and simulation of in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, microspheres move freely inside the dialysis sac at a very low speed, which prevents aggregation. In VDC, though microspheres do not move, they are placed in the buffered donor compartment in contact with a smooth surface, contrary to magnetically agitated dialysis bags (5). In this case, the release is actually a two-step process, the diffusion of LA through the polymer matrix and its subsequent diffusion from donor to receptor chamber.…”
Section: In Vitro Release Testing: Vertical Diffusion Cells and Rotatmentioning
confidence: 99%
“…This is in accordance with USP recommendations about the suitability of this equipment for delivery systems containing drugs with limited solubility (4). Dialysis tests performed with different devices may be useful for testing biodegradable microspheres (5). Different types of shaking and rotating devices have also been widely used for this purpose (6).…”
Section: Introductionmentioning
confidence: 99%
“…A Float-A-Lyzer ® (100 kDa MWCO 3 ml capacity, Spectra/Por ® ) was used for in vitro release kinetic studies (D'Souza and DeLuca, 2005). Preweighed amounts (10-60 mg) of protein-loaded freezedried microparticles were suspended in the release media (12 mM NaH 2 PO 4 ; 75 mM NaCI; 2 mM urea, and 62 mM imidazole pH 8) supplemented with 5 mM SDS as solubilising agent and 0.02% sodium azide as bacteriostatic agent.…”
Section: Determination Of In Vitro Protein Release Kineticsmentioning
confidence: 99%